Anti-hyperglycemic effects of Cissus quadrangularis extract via regulation of gluconeogenesis in type 2 diabetic db/db mice - Kim, Jeong-Won; Jeong, Ji-Soo; Kim, Jin-Hwa; Chung, Eun-Hye; Kim, Chang-Yeop; Lee, Dong-Ryung; Choi, Bong-Keun; Lim, Jong-Hwan; Ko, Je-Won; Kim, Tae-Won (Frontiers in Pharmacology, 2024)
Cissus quadrangularis is a vining plant widely used as a traditional herbal remedy for various ailments. In this study, the therapeutic effects of Cissus quadrangularis extract (CQR-300) on type 2 diabetes mellitus (T2DM) were investigated in a leptin receptor-mutated db/db mouse model.CQR-300 was orally administered to db/db mice (n = 6/group) at different doses (50 mg/kg, 100 mg/kg, and 200 mg/kg) for 8 weeks. Blood glucose levels and oral glucose tolerance were assessed using the AccuCheck glucometer. Enzyme-linked immunosorbent assay was performed to evaluate insulin and hemoglobin A1c (HbA1c) levels in the blood of db/db mice. Liver and pancreatic tissues from db/db mice were examined by hematoxylin and eosin (H&E) and immunohistochemical staining. The protein levels of gluconeogenesis-, lipogenesis-, and oxidative stress-related factors were evaluated using western blotting. CQR-300 treatment effectively reduced body weight, blood glucose, and insulin levels. HbA1c levels were increased by leptin receptor mutation. Additionally, in the oral glucose tolerance tests, the CQR-300 treated group had a faster blood glucose recovery rate than the db/db group. H&E and Oil red-O staining of the liver showed decreased lipid accumulation in the CQR-300 treated group than the db/db group. Western blot analysis confirmed that CQR-300 effectively inhibited gluconeogenesis, lipogenesis, and oxidative stress-related factors. Our findings suggest that CQR-300 has the potential to be used as a T2DM supplement.